1992
DOI: 10.1099/00222615-37-6-368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cell-wall teichoic acid with high-molecular-weight extracellular slime material from Staphylococcus epidermidis

Abstract: Summary. Extracellular high-mo1.-wt material was separated from liquid cultures of Staphylococcus epidermidis. This material contained protein c. 20 % w/w and polysaccharide c. 80 % w/w. The polysaccharide was isolated by gel and ion-exchange chromatography and contained glycerol phosphate, glucose, N-acetylglucosamine, and D-alanine. Cell-wall teichoic acid was isolated from strain RP-62A and had a similar composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Expression of the icaADBC operon depends on a variety of environmental conditions, and at least four unlinked genes (icaR, s B , the purR locus and SarA) are known to control PIA synthesis at the level of transcription (Conlon et al, 2002;Mack et al, 2000Mack et al, , 2007. However, cell-wall-linked Aap (accumulation-associated protein) and teichoic acids (Hussain et al, 1992) completely independent of PIA, consistent with the observation of ica-independent biofilms (O'Gara, 2007;Rohde et al, 2005).…”
Section: Introductionsupporting
confidence: 62%
“…Expression of the icaADBC operon depends on a variety of environmental conditions, and at least four unlinked genes (icaR, s B , the purR locus and SarA) are known to control PIA synthesis at the level of transcription (Conlon et al, 2002;Mack et al, 2000Mack et al, , 2007. However, cell-wall-linked Aap (accumulation-associated protein) and teichoic acids (Hussain et al, 1992) completely independent of PIA, consistent with the observation of ica-independent biofilms (O'Gara, 2007;Rohde et al, 2005).…”
Section: Introductionsupporting
confidence: 62%
“…The structural role of PIA and the EC TA in the extracellular matrix under different growth conditions was therefore investigated. Hussain et al (20) isolated an "extracellular high-molecular-weight carbohydrate polymer (EC)" from S. epidermidis RP62A grown in chemically defined medium and found that its composition was identical to that of the cell wall teichoic acid of this strain (19). In a recent study, we established the exact chemical structure of both EC and CW TAs of this strain (43).…”
Section: Vol 73 2005 Biofilm-producing Staphylococcus Exopolysacchamentioning
confidence: 99%
“…While cell wall (CW) TA is a common component of all gram-positive bacteria, extracellular (EC) TA has been discovered only in a limited number of species (10,23). Hussain et al (19) found that the chemical compositions of CW and EC TAs of S. epidermidis RP62A were very similar. Both TAs contained glycerol, phosphate, glucose, glucosamine, and D-alanine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bap homologs are also found in other bacteria, suggesting that the Bap family of surface proteins may have widespread importance in biofilm formation (Latasa et al 2005;Lasa and Penades 2006). S. aureus and S. epidermidis contain teichoic acids (TA), which are commonly found in many Gram-positive bacteria (Hussain et al 1992;Hussain et al 1993). TA can be linked to the cell wall in which case they are referred to as cell wall TA (WTA), or they can be linked to the cell membrane via a lipid anchor, known as lipoteichoic acid (LTA).…”
Section: Maturationmentioning
confidence: 99%